Mentally abused working women between disciplinary and arbitrary dismissals - Litouche, Dalila (Journal of Human Sciences, 2022)
The developments of life necessitated that women enter the world of work alongside men and bear the burdens equally with him, so she was subject to what the latter is subject to, but her specificity as a female was overshadowed and a number of ambitions emerged around her, especially from the employer if he was a man, who often subjected her to a sentence From psychological pressure as an aspect of moral violence to obey him and exploit the powers granted to him as an employer, and he may also take legal means that in fact involve moral violence, he may work to release her within the framework of what the law stipulates, taking advantage of her mistake, which may be serious and lead to her dismissal And the law controls the rights of workers, including women, but the same law may fall short in protecting the morally abused public woman, especially if it comes to the point of arbitrary dismissal and cutting off her source of livelihood.